Social Comparison and Risky Choices - Jona Linde; Joep Sonnemans (Tinbergen Institute, 2009)
This study attempts to combine two traditional fields in microeconomics: individual decision making under risk and decision making in an interpersonal context. The influence of social comparison on risky choices is explored in an experiment in which participants make a series of choices between lotteries with only positive outcomes. Three kinds of choice situations are employed. In the loss and gain context the social referent receives a fixed payoff that is respectively higher and lower than all possible payoffs of the decision maker. In the neutral context social referent and decision maker will always earn the same amount. In the gain and loss contexts the decision maker has no influence on the earnings of the social referent so strategic behavior or social preferences can play no role. We find that decision makers are more risk-averse in the loss context than in the gain context, with the behavior in the neutral context in between. This result is in opposition to the predictions of prospect theory extrapolated to a social context.
Keywords: C91; C92; D63; 330; Social comparison; social preferences; decision making under risk; experiment; Entscheidung bei Risiko; Glücksspiel; Risikoaversion; Soziales Verhalten; Test; Amsterdam